SRATEGI PENDIDIKAN BAHASA, SASTRA, BUDAYA DI SEKOLAH DAN MASYARAKAT MELALUI TRADISI KEBUDAYAAN - Eko Santosa (JURNAL IKADBUDI, 2013)
The cultures is very dynamic, its will goes to moves always. The cultures can became to moves and motivation for all mans. Its so to be doing and building hims of area. The building culture can’t lose from globalisation. The globalisation give many effision, easy  and freeland that have bigs interesting for the young. The Javanes culture to became losing,lose interested for himselft  of the culture.The pop cultures give lose effect of the tradisional culture. The reason on strategy culture was needed culture endure one there are javanes culture have losed from global culture. Keywords: The Education Strategy, Culture In School Sociaty